Get great marks for your essays / John Germov. - Germov, John (Allen & Unwin, 2000)
Unsure how to begin writing university essays? Then this book is for you. It provides the reader with the rules of essay writing, how to write drafts, handle references and do analysis, as well as giving shortcuts and time saving tips.